IMPLEMENTASI KURIKULUM MERDEKA DI SMAN 1 AMPEK ANGKEK TAHUN PELAJARAN 2022/2023 - Rina Andriyeni; Iswantir M (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract. This research is to find out and examine the "Implementation of the Merdeka Curriculum at SMAN 1 Ampek Angkek". This research was conducted using a phenomenological approach. This type of research is qualitative research which looks and hears in closer and more detailed explanations and individual understanding of their experiences. Approach This phenomenology is based on the researcher's interest in studying in more depth the phenomena experienced by the informants. The research was carried out at SMAN 1 Ampek Angkek. The informants in this research were teachers, principals and deputy principals , interviews and documentation studies. To ensure the validity of the data, several efforts were made as follows: (a) extending the data collection period, (b) carrying out continuous and serious observations, (c) carrying out triangulation, and (d) involving colleagues to discuss. From the results of the review in this research, it was found that 1) The principal and his teachers had the will to make changes, 2) SMAN 1 Ampek Angkek in its implementation used the Merdeka Mandiri Changed Curriculum Implementation. 3) the existence of an independent curriculum that becomes a reference in schools, which produces students who have noble character, independence, critical reasoning, creativity, mutual cooperation, and a sense of diversity. 4) School principals prepare their teachers by conducting training, technical guidance and workshops by bringing in resource persons from driving schools and from the province to increase teachers' insight and knowledge, fostering collaboration with teachers who support their leaders in participating in implementing the Independent Curriculum at SMAN 1 Ampek Angkek.